2002
DOI: 10.1051/0004-6361:20021612
|View full text |Cite
|
Sign up to set email alerts
|

Absorption systems in the spectrum of GRB 021004

Abstract: Abstract. We report on a 3600 s spectrum of GRB 021004 obtained with the Nordic Optical Telecope on La Palma 10.71 hours after the burst. We identify absorption lines from five systems at redshifts 1.3806, 1.6039, 2.2983, 2.3230, and 2.3292. In addition we find an emission line which, if due to Lyα from the host galaxy, gives a redshift of 2.3351. The nearest absorber is blueshifted by 530 km s −1 with respect to this line, consistent with shifts seen in Damped Lyα and Lyman-Break galaxies at similar redshifts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 18 publications
8
71
1
Order By: Relevance
“…A similar inference was made in the case of GRB 021004, which exhibited a complex velocity structure extending from about 140 to 3000 km s À1 (Möller et al 2002;Mirabal et al 2003;Schaefer et al 2003;Fiore et al 2005;Starling et al 2005b). The presence of such a fast outflow led to the general conclusion that the progenitor was a Wolf-Rayet star.…”
Section: A C Iv Outflowsupporting
confidence: 64%
“…A similar inference was made in the case of GRB 021004, which exhibited a complex velocity structure extending from about 140 to 3000 km s À1 (Möller et al 2002;Mirabal et al 2003;Schaefer et al 2003;Fiore et al 2005;Starling et al 2005b). The presence of such a fast outflow led to the general conclusion that the progenitor was a Wolf-Rayet star.…”
Section: A C Iv Outflowsupporting
confidence: 64%
“…Several absorption systems with outflow velocities of a few 1000 km s −1 were also reported (Salamanca et al 2002;Savaglio et al 2002) and studied in detail by Møller et al (2002b), Wang et al (2003), Matheson et al (2003), Schaefer et al (2003), Mirabal et al (2003), Starling et al (2005), and Lazzati et al (2006). Jakobsson et al (2005) also report the detection of the host galaxy Lyα line in narrow-band imaging.…”
Section: Introductionmentioning
confidence: 85%
“…1) exhibits a large number of absorption lines, as well as Lyα in emission (see Table 3 for a list, and also Møller et al 2002b;Starling et al 2005;Jakobsson et al 2005, on the Lyα emission line). Some of the absorption lines are due to two foreground systems at redshifts z = 1.3820 and z = 1.6020 (Møller et al 2002b;Mirabal et al 2003;see Tejos et al 2007see Tejos et al , 2009and Vergani et al 2009, for additional discussions about the foreground absorbers), but the remaining lines are from multiple systems found in the redshift range 2.2967 ≤ z ≤ 2.3291.…”
Section: The Blueshifted Absorption-line Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…Djorgovski et al 1998;Vreeswijk et al 2001b), that the afterglow is often situated behind a very large neutral hydrogen column (e.g. Hjorth et al 2003a;Vreeswijk et al 2004) with relatively high metal column densities and dust depletions compared to damped Lyα systems observed along QSO sight lines (Savaglio et al 2003;Savaglio & Fall 2004), and have provided evidence for high-velocity outflows (up to 3000 km s −1 , Møller et al 2002;Schaefer et al 2003;Mirabal et al 2003), presumably caused by the wind of the GRB massive-star progenitor. Finally, spectroscopic monitoring of GRB 030329/SN2003dh (Stanek et al 2003;Hjorth et al 2003b) has revealed a remarkable similarity with the spectral evolution of GRB 980425/SN1998bw (Galama et al 1998;Patat et al 2001), confirming the connection between GRBs and supernova explosions.…”
Section: Introductionmentioning
confidence: 99%